2017
DOI: 10.1186/s40201-017-0279-x
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of desalination by nanofiltration, reverse osmosis and integrated (hybrid NF/RO) membranes employed in brackish water treatment

Abstract: BackgroundAs an appropriate tool, membrane process is used for desalination of brackish water, in the production of drinking water. The present study aims to investigate desalination processes of brackish water of Qom Province in Iran.MethodsThis study was carried out at the central laboratory of Water and Wastewater Company of the studied area. To this aim, membrane processes, including nanofiltration (NF) and reverse osmosis (RO), separately and also their hybrid process were applied. Moreover, water physica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(19 citation statements)
references
References 23 publications
(32 reference statements)
2
15
0
2
Order By: Relevance
“…Results of this study agree to those of Silva et al [12] who reported that nanofiltration is equally effective as RO but lesser in energy consumption. Some other studies also support these findings [19,14,13].…”
Section: Water Productivitysupporting
confidence: 71%
See 2 more Smart Citations
“…Results of this study agree to those of Silva et al [12] who reported that nanofiltration is equally effective as RO but lesser in energy consumption. Some other studies also support these findings [19,14,13].…”
Section: Water Productivitysupporting
confidence: 71%
“…The quality of RO and nanofiltration indicated that any one of these two waters can be used for various purposes like drinking, irrigation of plants, landscaping, and industry. Earlier studies in Iran [13] indicated a major part of salt rejection into brine water by using nanofiltration, reverse osmosis, and hybrid processes. In their research, Na removal was better than Cl in case of both membranes as well as the hybrid system.…”
Section: The Quality Of Different Types Of Watermentioning
confidence: 99%
See 1 more Smart Citation
“…RO filters remove all salts dissolved in water, while NF filters, or nanofilters, create a selective mode of absorption of materials, giving us the right to choose the desired quality of water (Dach 2008). Several studies have proved that nanofiltration is even effective at low pressures; hence, it can be superior to reverse osmosis in similar conditions (Vaseghi et al 2016;Talaeipour et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In order to enhance desalination performance, diverse efforts are being applied with time. For instance, the coupling of membrane filtration (MF) techniques such as nanofiltration and reverse osmosis (NF/RO) is largely important to optimize cost and produced water quality whereby ionexchange (IX)/MF coupling improved product quality and it is applied in the selective removal of particular pollutants (Ang et al 2015;Esfahani et al 2016;Talaeipour et al 2017;Zaib and Fath 2013).…”
Section: Introductionmentioning
confidence: 99%